Biodanza as a Nonpharmacological Dance Movement–Based Treatment in Older People With Alzheimer's Disease: An Italian Pilot Study in 2 Tuscan Nursing Homes. Issue 5 (September 2021) - Chiesi, Fabrizio; Gori, Eleonora; Collini, Francesca; Palfrader, Angelo; Galli, Roberto; Guazzini, Andrea; Collodi, Stefania; Lorini, Chiara; Bonaccorsi, Guglielmo
Abstract : The aim of this pilot, feasibility study was to assess health improvements in 16 institutionalized older people with Alzheimer's disease, after the Biodanza intervention, a nonpharmacological dance movement-based treatment. Biodanza significantly decreased agitated and neuropsychiatric behaviors. Effectiveness studies will be performed in order to assess the implication of such interventions.